2018
DOI: 10.5812/mejrh.65828
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Method for Biological Activity Analysis of Recombinant Human Parathyroid Hormone-Related Protein

Abstract: Background: Parathyroid hormone-related protein (PTHrP) is a multi-functional protein with a sequence "aa 1-34" similar to that of parathyroid hormone (PTH). In spite of growth factor activity, there is no standardized analytical method to determine the biological activity of recombinant PTHrP. Methods: The current study isolated the cDNA encoding 141 N-terminal amino acid sequence of PTHrP, cloned it in plasmid vector pET32a, and produced recombinant PTHrP in Escherichia coli. The biological activity analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Chondrogenic differentiation is a phased process with an expression of early and late chondrogenic markers. ALP and type-X collagen are the most well-known markers of hypertrophy, a natural phenomenon during the terminal differentiation of mature chondrocytes before bone formation [ 212 – 214 ]. Le et al have selected seven patterns from a library of previously created microtopography platforms, which induced high ALP expression and used them to analyze the chondrogenic differentiation markers of ATDC5 cells [ 215 ].…”
Section: Reviewmentioning
confidence: 99%
“…Chondrogenic differentiation is a phased process with an expression of early and late chondrogenic markers. ALP and type-X collagen are the most well-known markers of hypertrophy, a natural phenomenon during the terminal differentiation of mature chondrocytes before bone formation [ 212 – 214 ]. Le et al have selected seven patterns from a library of previously created microtopography platforms, which induced high ALP expression and used them to analyze the chondrogenic differentiation markers of ATDC5 cells [ 215 ].…”
Section: Reviewmentioning
confidence: 99%
“…Nasrabadi et al 41 have reported the successful purification of recombinant BMP-2 using heparin-immobilized chromatography owing to the heparin-binding domain of BMP-2, whereas Gieseler et al 42 used cation exchange column chromatography. By using LC/MS-MS, we confirmed that all 8 tyrosine residues converted from Tyr to DOPA.…”
Section: Protein Synthesesmentioning
confidence: 99%
“…10,11,38 Although various approaches have been tested, the process of preparing biologically active BMP-2 dimers remains challenging. [39][40][41][42] The objective of the present study was to create an adhesive BMP-2 that can be stably adsorbed onto metals, such as Ti, to promote Ti binding to bones. We aimed to design a highly active adhesive and dimer-forming BMP-2 using bioorthogonal chemistry, wherein recombinant DNA technology was combined with enzymatic modifications to achieve long-term osseointegration with Ti.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation